Intracranial Angioplasty and Stenting before and after SAMMPRIS: “From Simple to Complex Strategy – The Chinese Experience” - Miao, Zhongrong (Frontiers in Neurology, 2014)
Intracranial atherosclerotic disease (ICAD) accounts for 33–50% of all ischemic strokes in the Asian population (1) and represents an important public health issue in China. The results of the SAMMPRIS trial alarmed most experienced interventionalists in China for two reasons. Firstly, the high complication rate in the stenting arm (20% the first year) was higher than expected. Secondly, the recurrent stroke rate in the aggressive medical treatment arm at 12.2% during the first year was unacceptably high, not to mention the fact that such tight vascular risk factor control is difficult to achieve for many patients in real life clinical experience, at least in China. The experience of treating ICAD in China, gained over the last two decades, is very rich and promising. We intend to highlight these past experiences and address future trials and trends in China. We will also address our criticism of the SAMMPRIS trial design in order to better design a future trial.